The financial position of English voluntary organisations: relationships between subjective perceptions and financial realities. (17th December 2018) - Mohan, John; Yoon, Yeosun; Kendall, Jeremy; Brookes, Nadia
Abstract : The financial position of English social policy charities has received much attention, with a particular focus on the difficulties that small- and medium-sized organisations are experiencing. However, in this article we show that the evidence base has a number of limitations. We then demonstrate, analysing data from a survey of more than 1, 000 charities, that organisational size, per se, is only one dimension of the problem: perceptions that the operating and financial environment is challenging are related to other organisational characteristics. We then add to the survey data indicators of financial vulnerability to investigate whether there is a relationship between perception (responses to questions about the resources available to charities) and financial reality (the recent financial history of these charities). Somewhat reassuringly, however, we demonstrate that there is a degree of consistency between the perceptions that organisations report and we discuss the implications of the findings.